TUTURAN IMPERATIF DALAM UNGKAPAN DI BAK TRUK PADA PERJALANAN MUNCAR-BLOKAGUNG BANYUWANGI (KAJIAN SOSIOPRAGMATIK) - Ali Manshur; Gatut Setiadi Gatut Setiadi; Syafi' Junadi Syafi' Junadi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research discusses the imperative speech act of written expressions on the truck bed on the Muncar-Blokagung Banyuwangi journey. The main focus of this research was observing the language of the expressions in the trucks on the Muncar-Blokagung Banyuwangi journey. This research uses a sociopragmatic approach and qualitative descriptive research methods. A sociopragmatic approach is used to study the use of language expressions in various social contexts. The research aims to determine the variety of imperative utterances found in truck beds. The results of this research found that there were twenty-seven imperative utterances. Of the twenty-seven imperative utterances, there are nine forms of imperative utterances. It is hoped that this research can provide new insights into imperative speech forms. As well as providing recommendations to readers of this work to be able to use this research as a reference source for sociopragmatic studies in the future